Error Analysis Found in Students’ Writing Composition of Simple Future Tense - Tira Nur Fitria (Hasanuddin University, 2018)
Error analysis is a way to investigate errors in the second or foreign language acquisition. This study of error (error analysis) is part of an investigation of the process of English language learning. This research will find the kind of error analysis found in students’ writing composition in the aspects of grammar, punctuation, and spelling and to find the most dominant kind of error analysis found in students’ writing composition of simple future tense. This research used the qualitative research to collect empirical data from the students’ written. By using this method, the data would be accurately collected. The object of the research is fifteen students’ writing composition which taken from 15 students of S1 Accounting STIE AAS Surakarta. The result of analysis shows that the students’ error in writing composition of simple future tense consists of three aspects of writing. First, in grammar, punctuation and spelling. In grammar aspect, there are errors in some points of class word like in noun (21 data or 36,84 %), determiner/article (2 data or 3,51 %), pronoun (1 data or 1,75 %), preposition (15 data or 26,32 %) and verb (18 data or 31,58 %), then the most dominant error in grammar aspect is noun. Second, in punctuation (16 data or 17,20%). Third, in spelling (20 data or 21,51%). Based on the frequency of each aspect of error writing shows that the most dominant error found in the students’ writing composition is in the aspect of grammar as 57 data or 61,29.